Analisis Dan Penerapan Jaringan Hotspot Server Berbasis Mikrotik Di Gedung Sekolah Smk Swasta Gebang - Hasanuddin; Sumarlin; Ita Margaretta Br Tarigan (Institut Teknologi dan Bisnis Indonesia, 2026)
Gebang Private Vocational School faces obstacles in managing the internet network, including uneven bandwidth distribution, difficulties in monitoring internet usage, and inadequate network security. The purpose of this study is to analyze and implement a MikroTik-based server hotspot network at Gebang Private Vocational School to improve the efficiency of network management, security, and internet service quality. This research uses observation, literature study, and design methods. The research stages include needs analysis, network topology design, MikroTik router configuration, server hotspot implementation, and system testing and evaluation. The result of this study is that the MikroTik-based server hotspot network has succeeded in improving bandwidth management, network security, and ease of monitoring internet usage. This system allows for restriction of user access, fairer distribution of bandwidth, and increased speed and stability of internet connections throughout school areas. Researchers suggest conducting periodic monitoring and maintenance of the system that has been implemented and provide training to school IT staff regarding the management and troubleshooting of the MikroTik system.